2005
DOI: 10.1007/s11136-004-4782-z
|View full text |Cite
|
Sign up to set email alerts
|

The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30): Validation of English version in Singapore

Abstract: This study provides preliminary evidence for the validity and reliability of the EORTC QLQ-C30 in English-speaking Singaporean cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 25 publications
(24 reference statements)
10
86
0
1
Order By: Relevance
“…The cognitive functioning scale showed poor internal consistency at all levels of analysis. Our findings were similar to several other validation studies involving the EORTC QLQ-C30 in many Asian countries and language settings such as China (Cheng et al, 2011), Indonesia (Perwitasari et al, 2011), Singapore (Luo et al, 2005), Korea (Yun et al, 2004), Turkey (Guzelant et al, 2004), Iran (Hajebrahimi et al, 2013), and Malaysia (breast cancer) (Yusoff N et al, 2010). All these studies reported a poor internal consistency coefficient for the cognitive functioning scale (Cronbach's alpha ranges from 0.19 to 0.67).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The cognitive functioning scale showed poor internal consistency at all levels of analysis. Our findings were similar to several other validation studies involving the EORTC QLQ-C30 in many Asian countries and language settings such as China (Cheng et al, 2011), Indonesia (Perwitasari et al, 2011), Singapore (Luo et al, 2005), Korea (Yun et al, 2004), Turkey (Guzelant et al, 2004), Iran (Hajebrahimi et al, 2013), and Malaysia (breast cancer) (Yusoff N et al, 2010). All these studies reported a poor internal consistency coefficient for the cognitive functioning scale (Cronbach's alpha ranges from 0.19 to 0.67).…”
Section: Discussionsupporting
confidence: 91%
“…This indicated that, in our setting, a few of the EORTC QLQ-C30 scales differentiated between patients on the dichotomized performance scale. This is comparable to studies in Indonesia (Perwitasari et al, 2011) and Singapore (Luo et al, 2005). However, the Korean version of the EORTC QLQ-C30 reported a significant difference between patients in subgroups of performance scale as measured using the Eastern Oncology Group (ECOG) scale.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other studies showed similar values, ranging from 0.62 to 0.94 [6][7][8]10,23 . For the BR23 module, internal consistencies for functional and symptom scales were 0.78 and 0.83, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…As QOL involves multiple respects such as health, culture, belief, and value, its measurement methods also vary; among these varied methods, questionnaire is a generally-adopted one. Presently, there are two kinds of rating scales which are used for measuring the influence of tumors on QOL: One kind is rating scales used for measuring the QOL of patients with various tumors (such as EORTC-QLQ-C30 proposed by the European cancer treatment study group), and the other is rating scales for measuring the QOL of patients with specific tumors (such as EORTC QLQ-OES18 for patients with EC and EORTC QLQ-BR23 for those with breast cancer) (Blazeby et al, 2003;Luo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%